The complexity of genetic variation in a simple immune system. - Kwiatkowski, D (2005)
Fruitflies derived from a wild population vary in their resistance to infection with the bacterial pathogen Serratia marcescens. A survey of nucleotide diversity in 21 genes involved in innate immunity concluded that 16 genes had polymorphisms associated with resistance to this specific pathogen. However, the effects of individual polymorphisms on the resistance phenotype were modest, and epistatic interactions appeared to be common. What might these findings tell us about genetic resistance to infection in humans?